A comparative study of the effectiveness of price support and fertilizer subsidy programmes for self-sufficiency in rice production in Peninsular Malaysia - Sulong, Ismail (1984)
Rice production is of both economic and political importance to the Malaysian government. Despite the implementation of various programmes the country is still unable to be self-sufficient in rice production. Among the policy programmes implemented and aimed at achieving self-sufficiency in rice production and simultaneously increasing the farmers' incomes, are two short term policy programmes namely price support and fertilizer subsidy schemes. Both schemes have incurred heavy expenses on the part of the government, but more so, the self-sufficiency level in rice output could not be achieved while the incidence of poverty among padi farmers still remains amongst the highest in the country's various occupational sectors. The purpose of this study is to determine the effectiveness of each of the two policy programmes in their contribution towards achieving self-sufficiency in rice production and increasing the farmers' income. Previous research have shown that both price support and fertilizer subsidy schemes could increase crop output and consequently increased the farmers' income. A finding of a comparative study on price support and fertilizer subsidy policy programmes to achieve self-sufficiency in rice production in the Philippines showed that the fertilizer subsidy scheme is more cost effective and contributes a higher income for the farmers than that of the price support scheme. The present study adapts the model used by Barker and Hayami in the Philippines study. Secondary data and information from previous studies are used to evaluate the costs and benefits of the two policy programmes in the study.